Aesthetic Views of Antanas Maceina - Baltuškaitė, Marija (Respectus Philologicus, 2001)
Maceina’s aesthetical views belong to one of the most known modern irrational theories of the art philosophy - to the existentialism art philosophy "as existentialists maintain, creation of art, and aesthetical experience are one of the methods for a human to strive for the authentic existence".The art reasoning of the most known Lithuanian philosopher leans upon the philosophy of religion, which is shown in his published book "The philosophy of religion". Leaning upon M. Heidegger’s existence ontology, a question about existence Maceina appreciates just religiously: "God is a foundation for the human’s existence, and human in the God’s respect is the grounded existence".Maceina, the same as M. Heidegger, thinks that poetry can to reveal "the meaning of existence" in the most perfect manner, that’s why it’s the highest sort of art. As the thinker thinks, the work of poetry- a decision for the eternity problems. According to Maceina’s ontological conviction, philosophy and poetry are merged by general origin - language, but at the same time the "humanistic apprehension of existence and experience". Namely this authentic notion of existence creates the depth of a poem, makes poets to become as individuals, and their works - as values of art, not mere emblems.According to the thinker, the real artist will always collide with a problem of God. This axiom is the starting point for A. Jasmantas poetical thinking, which exists in the system of Christian values. Apparently, this system of values determines the universal poetical discourse regarding our existence on the Earth, which is created by metaphorical of soulful landscape’s existence and Bible marks.